Impact of implementing novel automated code blue activation system on in-hospital cardiac arrest: A single center study. (December 2020) - Khan, Faheem Ahmed; Lyu, Ting; Lee, Eng Kiang; Dhanvijay, Shekhar; Kansal, Amit; Kansal, Monika Gulati; Tan, Rou An; D'Souza, Jared; Lee, Yee Shay; Lim, Nicholas; Liew, Mei Pheng; Cerdana, Ian; et al.
Abstract: Background: Prompt identification and management of patients having clinical deterioration on wards is one of the key steps to reduce in-hospital cardiac arrests (IHCA). Our organization implemented a novel Automated Code Blue Alert and Activation (ACBAA) system since 1st March 2018. Methods: We conducted a retrospective before-and-after ACBAA system implementation study in JurongHealth Campus (JHC) of National University Health system (NUHS), Singapore. In JHC, code blue can be activated by both manual activation and ACBAA system activation from 1st March 2018. The ACBAA system will be activated when any of the pre-defined peri-arrest criteria is met. The primary outcome of the study was the incidence of IHCA. The secondary outcome included return of spontaneous circulation (ROSC) of IHCA and in-hospital survival to home discharge of code blue activation. Outcomes: The incidence of IHCA per 1000 hospital admissions after-ACBAA system implementation was 14.6% lower than before-ACBAA system though not statistically significant [relative risk (RR): 0.86, 95% confidence interval (CI) 0.55−1.34, P > 0.05]. Compared to the before-ACBAA system period, the after-ACBAA system period had a trend for higher rate of survival to home discharge after IHCA (RR: 2.13, 95% CI 0.65−6.93, P > 0.05) with good neurological outcome. Conclusions: Implementation of a novel ACBAA system has shown a trend in reducing IHCA incidence. In the era of digitalised healthcare system, the ACBAA system is practical and advisable to implement in order to reduce IHCA. Further studies are required to validate the criteria for peri-arrest code blue activation.